ANALISIS PREFERENSI SISWA MELANJUTKAN KE MTS AN NUR KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR TAHUN PELAJARAN 2014/2015 - Purwo Sucipto Purwo Sucipto; Elni Yakub Elni Yakub; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimsto: (a) to analyze the aspects of internal preference actorin to student schoose MTs AnNur Perhentian Raja District of Kampar, (b) to analyze aspects of preference External factorsthata student choose MtsAnNur Perhentian Raja District of Kampar, (c) Analyze category MTs AnNur Perhentian Raja District of Kampar, (d) Analyze the categoryof external factorsinto the preferencesof MTs AnNur Perhentian Raja District of Kampar,The method usedin this studyis adescriptive study, the technique of saturated samples (total sampling). Theresults ofthis study are: (a) Internal factors become dominant preferences of MTs AnNur Perhentian Raja District of Kampar TP.2014/2015 is because of my desire the valueof 100%. (b) external factors which become MTs AnNur Perhentian Raja District of Kampar TP. 2014/2015 is locate don indicator desire of schools the excelinallfields 76,83%. (c) Category internal factors become the preference of MTs AnNurPerhentian Raja District of Kampar TP. 2014/2015 in the high category.. (d) Category external factors into the preferences of MTs AnNur Perhentian Raja District of Kampar TP. 2014/2015 is locatedon the lower category. Keywords: Preferences